The manifestation of government strategic communication through social media / Nor Suraiti Madianuddin and Noor Nirwandy Mat Noordin - Madianuddin, Nor Suraiti; Mat Noordin, Noor Nirwandy (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2018)
The development of strategic communication in social media is something that is ideal to be discussed and this matter is considered vital. This includes planning and analysing issues that are often being debated at national level to which it will inevitably lead to difficulties in regulating the information that exists in the cyberspace. Apparently, the movement to become vocal and open in expressing opinions through social networking sites begin during Malaysia's 12th General Election back in 2008. This study is very important to delineate the elements of government strategic communication through social media and at the same time to clarify the strength and weaknesses of the strategic. This study wishes to improve the current government strategic communication through social media by addressing the correct message through convincing storytelling-technique as to face current challenges in the future. It is important for the current government to upgrade and develop new skills on government strategic communication through social media and it is hoped that there will be an in-depth study of Anti Fake News and its impact on the sentiment especially in changing public perception and social convention on norms.